Self-referentiality in Orson Welles’ Sketch Book (1955): Similarities and Parallels with YouTuber Narrative - Giménez Sarmiento, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Orson Welles created "Orson Welles' Sketch Book" in March 1955, a documentary series for the British BBC. It consisted of six episodes, each lasting fifteen minutes, where Welles shared a series of personal anecdotes accompanied by sketches he drew himself. Despite the apparent simplicity of the concept, Welles implemented a set of strategies where self-reference stood as a fundamental driving force of the narrative. Nearly seventy years later, we can observe that this approach is remarkably similar to that adopted by the majority of so-called YouTubers, content creators who utilize social media to disseminate their messages. Through an analysis of the content of these programs, we will extract the self-references made by Orson Welles and compare them with some of the studies conducted on this type of storytelling.